Factorial validity of the Maslach Burnout Inventory (MBI-HSS) among Spanish professionals - Gil-Monte,Pedro R (2005)
OBJECTIVE: To assess the factorial validity and internal consistency of the Maslach Burnout Inventory (MBI-HSS). METHODS: In a sample consisting of 705 Spanish professionals from diverse occupational sectors (health, education, police and so one), seven plausible factorial models hypothesized were compared using LISREL 8. RESULTS: The four-factor oblique solution and the three-factor oblique solution showed the best and similar fit. Deletion of Item 12 and Item 16, taking into consideration the suggestions in the manual, improved the goodness of fit for both models. The four-factor oblique model suggests that, in addition to Emotional Exhaustion (EE) and Depersonalization (DP), Personal Accomplishment (PA) consists of two components labeled here Self-Competence (Items 4, 7, 17, and 21) and the Existential Component (Items 9, 12, 18, and 19). However, the alpha coefficient was relatively low for the Self-Competence component, suggesting that it is more suitable to estimate the syndrome as a threedimensional construct. The Cronbach's alpha was satisfactory for PA (alpha =.71) and EE (alpha =.85), and moderate for DP (alpha =.58). CONCLUSIONS: The results show that the MBI-HSS offers factorial validity and its scales present internal consistency to evaluate the quality of working life for Spanish professionals.